2019
DOI: 10.1088/1748-9326/ab1cf1
|View full text |Cite
|
Sign up to set email alerts
|

Large greenhouse gas savings due to changes in the post-Soviet food systems

Abstract: As the global food system contributes significantly to global greenhouse gas (GHG) emissions, understanding the sources of GHG emissions embodied in different components of food systems is important. The collapse of the Soviet Union triggered a massive restructuring of the domestic food systems, namely declining consumption of animal products, cropland abandonment, and a major restructuring of agricultural trade. However, how these complex changes have affected global GHG emissions is uncertain. Here, we quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…By the end of 1995, over 35% of the Russian population was living below the official poverty line 57 . The associated changes in food consumption, especially beef, and the vegetation recolonization of abandoned cropland resulted in a net cumulative reduction of carbon dioxide emissions 58 . The financial crisis resulted in the collapse of the ruble in August 1998, even though other European ex-communist republics experienced substantial economic growth during the same time period 56 .…”
Section: Discussionmentioning
confidence: 99%
“…By the end of 1995, over 35% of the Russian population was living below the official poverty line 57 . The associated changes in food consumption, especially beef, and the vegetation recolonization of abandoned cropland resulted in a net cumulative reduction of carbon dioxide emissions 58 . The financial crisis resulted in the collapse of the ruble in August 1998, even though other European ex-communist republics experienced substantial economic growth during the same time period 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In another process, land that was formerly grazed for many decades is now only being lightly grazed or not at all. Secondly, there have been investigations of how land use changes have affected carbon sequestration in plants and soil, mainly due to abandonment of cropping in the former Virgin Lands region of northern Kazakhstan and some return of livestock grazing (Perez-Quezada et al, 2010;Kurganova et al, 2015;Schierhorn et al, 2019). Thirdly, there are studies on the biodiversity implications of the radically altered livestock grazing pressure patterns and crop cessation (Kamp et al, 2009(Kamp et al, , 2011(Kamp et al, , 2015(Kamp et al, , 2016.…”
Section: Environmental Impacts Of Livestock Management In the Post-soviet Periodmentioning
confidence: 99%
“…As rainfed cropping sharply declined with the absence of state support after the end of the USSR, by 2000 about 40% of arable land in Kazakhstan had been withdrawn from cropping over two decades (Kamp et al, 2011;Dara et al, 2020). Some 14.1 Mha of abandoned crop land remains uncultivated (Schierhorn et al, 2019). Over the same period, as has been discussed here, livestock numbers crashed, most of the remaining livestock could not be taken to remote pastures, and instead had to be grazed around villages (Behnke, 2003;Robinson and Milner-Gulland, 2003b;Robinson et al, 2016).…”
Section: Rangeland Vegetation Transformationsmentioning
confidence: 99%
“…A similar effect was observed in history earlier during the collapse of the Soviet Union in 1991. There was a signi cant reduction in greenhouse gases attributed to the reduction in meat consumption following the economic slowdown (Schierhorn et al 2019). A study from California showed that economic indicators had a statistically signi cant effect on air pollution levels (Davis 2012).…”
Section: Introductionmentioning
confidence: 99%